The Hijazi Inequalities on Complete Riemannian Spinc Manifolds - Roger Nakad (Advances in Mathematical Physics)
We extend the Hijazi type inequality, involving the energy-momentum tensor, to the eigenvalues of the Dirac operator on complete Riemannian Spinc manifolds without boundary and of finite volume. Under some additional assumptions, using the refined Kato inequality, we prove the Hijazi type inequality for elements of the essential spectrum. The limiting cases are also studied.